A Look at the United States 101st Colored Infantry and the Free Life of John Sullivan - Cunningham, Phil (Kansas State University. Dept. of History. Chapman Center for Rural Studies, 2010)
Phil Cunningham provides a bio-sketch of former African American Union soldier John Sullivan, who farmed in southern Wabaunsee County in the 1880s. A member of the 101st Tennessee Colored Infantry, formed in western Tennessee to support the Union cause, Sullivan and fellow veterans endured the violence of Reconstruction. Sullivan, the son of a slave and a plantation owner, migrated to Kansas and became a successful homesteader and community member. A group of Tennessee black Union soldiers is buried in Eskridge Cemetery. The author includes interviews with descendents and an analysis and photos of Sullivan's headstone insignia.
Keywords: African American; Wabaunsee County; Black soldiers; Eskridge